Cinnamic acids derived compounds with antileishmanial activity target Leishmania amazonensis arginase. (10th October 2018) - da Silva, Edson Roberto; Brogi, Simone; Grillo, Alessandro; Campiani, Giuseppe; Gemma, Sandra; Vieira, Paulo Cezar; Maquiaveli, Claudia do Carmo
Abstract: This study describes the activity of five natural hydroxycinnamic acids and derived compound: caffeic (1 ), rosmarinic (2 ), chlorogenic (3 ), and cryptochlorogenic (4 ), acids and isoverbascoside (5 ). All compounds inhibited Leishmania amazonensis arginase with IC50 —in range of 1.5—11 μM. Compounds2 and5 also showed activity against promastigotes of L. amazonensis with IC50  = 61 (28–133) μM and IC50  = 14 (9–24) μM, respectively. Further computational studies applying molecular docking simulations were performed on the competitive inhibitors to gain insight into the molecular basis for arginase inhibition and could be exploited to the development of new antileishmanials drug targeting parasite arginase. Abstract : Cinnamic acids derived compounds inhibited Leishmania arginase. Free binding energies (Δ G bind ) indicate higher affinity with the parasite arginase rather than human arginase. Compound5 showed better result against promastigotes.